Two Bobbies : a true story of Hurricane Katrina, friendship, and survival - Larson, Kirby; Nethery, Mary.; Cassels, Jean (New York : Walker, 2008)
Tells the true story of Bobbie the dog and Bob Cat, two pets who bonded together and were able to survive the devastation of Hurricane Katrina.
2.2
K-3
Keywords: Dogs -- Anecdotes -- Juvenile literature; Cats -- Anecdotes -- Juvenile literature; Hurricane Katrina, 2005 -- Anecdotes -- Juvenile literature; Dogs -- Anecdotes; Cats -- Anecdotes; Hurricane Katrina, 2005 -- Anecdotes; Dogs -- Anecdotes; Cats -- Anecdotes; Hurricane Katrina, 2005 -- Anecdotes